2017
DOI: 10.1016/j.jacc.2017.09.1111
|View full text |Cite|
|
Sign up to set email alerts
|

Abdominal Obesity Is Associated With an Increased Risk of All-Cause Mortality in Patients With HFpEF

Abstract: The risk of all-cause mortality was significantly higher in patients with HFpEF with abdominal obesity than in those without abdominal obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
126
2
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 44 publications
7
126
2
5
Order By: Relevance
“…Recent studies have identified distinct high‐risk clinical phenotypes in patients with HF . Specifically, the ‘obesity phenotype’ has been associated with greater impairments in cardiac structure and function, worse symptom burden, and higher risk of HF hospitalization . In a recent analysis from the TOPCAT trial cohort, abdominal obesity was associated with significantly higher risk of adverse events among patients with HFpEF with no significant interaction between spironolactone use and abdominal obesity .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have identified distinct high‐risk clinical phenotypes in patients with HF . Specifically, the ‘obesity phenotype’ has been associated with greater impairments in cardiac structure and function, worse symptom burden, and higher risk of HF hospitalization . In a recent analysis from the TOPCAT trial cohort, abdominal obesity was associated with significantly higher risk of adverse events among patients with HFpEF with no significant interaction between spironolactone use and abdominal obesity .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the ‘obesity phenotype’ has been associated with greater impairments in cardiac structure and function, worse symptom burden, and higher risk of HF hospitalization . In a recent analysis from the TOPCAT trial cohort, abdominal obesity was associated with significantly higher risk of adverse events among patients with HFpEF with no significant interaction between spironolactone use and abdominal obesity . Similarly, the ‘diabetes phenotype’ in patients with HFpEF has also been associated with higher symptom burden and greater risk of adverse outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…Both obesity and type 2 diabetes are important risk factors for the development of heart failure (HF) with preserved ejection fraction (HFpEF) . Of patients with established HFpEF, 70–80% are obese, and nearly half have type 2 diabetes . However, the diagnosis of HFpEF can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators contend that HFpEF, in obesity, may even be a distinct form of heart failure that may require specific treatment . Furthermore, abdominal obesity is associated with an increased mortality in patients with HFpEF . Amongst many of its characteristics, obesity has been viewed as a hypoxic state .…”
Section: Introductionmentioning
confidence: 99%